1986
DOI: 10.1002/bit.260280606
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of southern red oak hemicelluloses and lignin in a mild sulfuric acid hydrolysis

Abstract: Removal and modification of southern red oak hemicelluloses and lignin in a 0.05%(w/v) sulfuric acid hydrolysis were investigated. The hydrolysis profile was to raise the reaction from room temperature to 150 degrees C for in 38 min and to extend the hydrolysis at 150 degrees C for 1 h. At the end of the hydrolysis, 25.5% of red oak components were dissolved, of which 58% was xylose and 17% lignin. As the hydrolysis proceeded from room temperature to 150 degrees C, a part of red oak xylan was removed to yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In general, because of its branched structure and lower degree of polymerization, hemicelluloses are more susceptible to hydrolysis than cellulose. ,,− It is to be expected then that the hemicellulose fraction of biomass is degraded faster than the cellulose fraction. This was observed by Tran and Chambers during mild sulfuric acid hydrolysis of southern red oak at 150 °C as well as in the hydrothermal processing of lignocellulosic materials between 150−230 °C in the study made by Garrote and others . In a study reported by Karagoz et al on biomass liquefaction, it was shown that mainly phenolic compounds are found in the bio-oil of wood biomass when it is treated with different bases and their salts at 280 °C for 15 min.…”
Section: Introductionmentioning
confidence: 62%
“…In general, because of its branched structure and lower degree of polymerization, hemicelluloses are more susceptible to hydrolysis than cellulose. ,,− It is to be expected then that the hemicellulose fraction of biomass is degraded faster than the cellulose fraction. This was observed by Tran and Chambers during mild sulfuric acid hydrolysis of southern red oak at 150 °C as well as in the hydrothermal processing of lignocellulosic materials between 150−230 °C in the study made by Garrote and others . In a study reported by Karagoz et al on biomass liquefaction, it was shown that mainly phenolic compounds are found in the bio-oil of wood biomass when it is treated with different bases and their salts at 280 °C for 15 min.…”
Section: Introductionmentioning
confidence: 62%
“…It is clear that the investigated systems only address very specific cases where cellulose and fatty acid esters of lignin are physically mixed, while in real systems the lignin is covalently attached to, for example, hemicelluloses. Although a wide range of acetylated lignins has been reported, , fatty acid esters involving lignins account for a rather low proportion of the total lignin and it is not sure whether they exist in nature at all. , However, there are other aromatic compounds such as suberins and urushiols where phenolic fatty acid esters are major constituents determining the structure and the function of cell wall components (e.g., cork). Moreover, it is assumed by some authors that suberins may be linked covalently to polyaromatic compounds such as lignins. , …”
Section: Discussionmentioning
confidence: 99%
“…The mean lignin concentration of the four-year-old woodchips at each location along the length of the bed ranged from 26.9% ± 0.75 (at 79.6 m) to 31.0% ± 0.78 (at 0 m) (table 1). As the woodchips were identified as hardwood (i.e., White Elm, Cottonwood, and Red Oak), we expect that the initial lignin concentration ranged from 22% to 24% (Pettersen, 1984;Rowell, 2013;Tran and Chambers, 1986).…”
Section: Carbon Quality Lignin and Cellulose Concentrationsmentioning
confidence: 99%